+0  
 
0
72
1
avatar

If x^2 - 77x + c = (x + a)^2 for some constants c and a, find a.

 May 29, 2021

Best Answer 

 #1
avatar+34340 
+2

epand R side   x^2 + 2a x+ a^2

equating to L side   shows    2a = -77     ( the 'x' coefficients)

                                            a = -38.5

 

                                        and a^2 = c        so c = (-38.5)^2 = 1482.25

 

 

      ( x-38.5)^2   = x^2 - 77x + 1482.25

 May 29, 2021
 #1
avatar+34340 
+2
Best Answer

epand R side   x^2 + 2a x+ a^2

equating to L side   shows    2a = -77     ( the 'x' coefficients)

                                            a = -38.5

 

                                        and a^2 = c        so c = (-38.5)^2 = 1482.25

 

 

      ( x-38.5)^2   = x^2 - 77x + 1482.25

ElectricPavlov May 29, 2021

51 Online Users

avatar
avatar
avatar